2020
DOI: 10.7150/jca.47549
|View full text |Cite
|
Sign up to set email alerts
|

Design and biological evaluation of novel BF-30 analogs for the treatment of malignant melanoma

Abstract: Aims: To evaluate anti-tumour effects and mechanism of novel BF-30 derivative via cell-based assays and melanoma-bearing model mice. Main methods: BF-30 derivatives were designed by fusing heptapeptide-palmitic tags to native BF-30 via a protease-cleavable linker and prepared by F-moc solid-phase synthesis. Albumin binding affinity test and in vitro control-released assay were performed to screen these BF-30 derivatives and explore the mechanism of anti-tumour effects. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In vivo experiments, BF-30 obviously inhibited melanoma development in B16F10 tumor-bearing mice without adverse reactions occurring ( Wang et al, 2013 ). In addition, Qi et al (2020) designed a BF-30 derivative, LBF-14, which exhibited significant anti-melanoma action through disrupting the cell membrane, and then binding to the genomic DNA to suppress the migration and angiogenesis of melanoma cells.…”
Section: Animal Sources Of Amps With Anticancer Activitymentioning
confidence: 99%
“…In vivo experiments, BF-30 obviously inhibited melanoma development in B16F10 tumor-bearing mice without adverse reactions occurring ( Wang et al, 2013 ). In addition, Qi et al (2020) designed a BF-30 derivative, LBF-14, which exhibited significant anti-melanoma action through disrupting the cell membrane, and then binding to the genomic DNA to suppress the migration and angiogenesis of melanoma cells.…”
Section: Animal Sources Of Amps With Anticancer Activitymentioning
confidence: 99%
“…The molecule was also tested in a mouse cancer model, showing a significant suppression in melanoma growth and improved survival rates of B16F10-bearing mice. Cytotoxicity was analyzed in vivo in rhesus monkeys and showed that the modified version was less toxic and presented an increased half-live in comparison with the native AMP ( Qi et al, 2020 ).…”
Section: Cathelicidins and Cancer Therapymentioning
confidence: 99%
“…The molecule was also tested in a mouse cancer model, showing a significant suppression in melanoma growth and improved survival rates of B16F10-bearing mice. Cytotoxicity was analyzed in vivo in rhesus monkeys and showed that the modified version was less toxic and presented an increased half-live in comparison with the native AMP (Qi et al, 2020).…”
Section: Cathelicidins and Cancer Therapymentioning
confidence: 99%